Bad things - Marshall, Michael, 1965 May 3- ([New York] : William Morrow, 2009)
Three years after losing his four-year-old son in a bizarre accident involving a lake jetty, John finds his precarious hold on a normal life destabilized when he receives an e-mail from a stranger claiming to know the truth, a situation that triggers a terrifying sequence of events.
Keywords: Fathers -- Fiction; Missing children -- Fiction; Psychological fiction; Suspense fiction